MODEL REGRESI MULTIVARIAT UNTUK MENENTUKAN FAKTOR-FAKTOR YANG MEMENGARUHI KESEJAHTERAAN KABUPATEN/KOTA DI KALIMANTAN SELATAN - Syifa Urrahmah; Fuad Muhajirin Farid; Maisarah Maisarah (RAGAM: Journal of Statistics & Its Application, 2023)
The purpose of a region to carry out development is to realize prosperity. In measuring a welfare is the coverage of APBD funds such as Local Own Revenue and others that can be influenced. The analysis that can be used in research is multivariate regression. The purpose of the research is to find out what factors affect welfare in South Kalimantan in 2018-2020. Based on the analysis, the multivariate regression model has two factors that are thought to influence PAD and PDRB, namely personnel spending and special allocation funds with modeling   with goodness-of-fit testing it can be explained that the relationship between variables is 76.51%. Keywords: Welfare. PAD, PDRB, Personnel Expenditures, Multivariate